Varia epigraphica del País valenciano - Corell, Josep (Fortunatae: Revista canaria de Filología, Cultura y Humanidades Clásicas, 1992)
The authors present sir inscriptions here: about the two first, that are commonly considered falle, they want to reivindicate their authenticity or, at least, to make evident that their falseness is not sure; on the other hand, they correct the lecture of the two following; the other two are inedited.